Liberal Muslim interpretation of Islamic Shari’a : an analysis - Faiz Hadi Sanadi,; Mazlan Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the context of interpreting a verse of the Qur’an, the exegetes has put in place some guidelines to ensure that each interpretation is in line with the Qur’an and Sunnah. This set of guidelines was created to avoid any inconvenience to these verses of the Qur’an especially to Muslim liberals. This is because the liberals often interpret a verse based on their (hermeneutical) reasoning and their interpretation is seen only in the context of the verse without reference to the definitive scriptures. Interpreting the Qur’an means trying to explain a verse and the contents of the Qur’an in it for clarity. This study is a qualitative study using a document analysis approach and proofreading books. Therefore, in this study, there are three objectives of the study that will be of interest to study. First, the criticism of the liberal Muslims regarding inheritance rights division found in the Qur’an. Second, a critique of hand-cut punishment in hudud law. Third, criticism of female aurah. The study found that among the things criticized by liberal Muslims were criticism of inheritance rights, criticism of the of hand-cut punishment law (hudud) and female aurah. This shows that these liberal Muslims are trying to interpret and revise the laws found in the Qur’an to suit their liberal point of view.